Modeling Soil-Facing Interface Interaction With Continuum Element Methodology - Damians, Ivan P.; Olivella, Sebastià; Bathurst, Richard J.; Lloret, Antonio; Josa, Alejandro (Frontiers in Built Environment, 2022)
Soil-facing mechanical interactions play an important role in the behaviour of earth retaining walls. Generally, numerical analysis of earth retaining structures requires the use of interface elements between dissimilar component materials to model soil-structure interactions and to capture the transfer of normal and shear stresses through these discontinuities. In finite element method software programs, soil-structure interactions can be modelled using “zero-thickness” interface elements between the soil and structural components. These elements use a strength/stiffness reduction factor that is applied to the soil adjacent to the interface. However, in some numerical codes where the zero-thickness elements (or other similar special interface elements) are not available, the use of continuum elements to model soil-structure interactions is the only option. The continuum element approach allows more control of the interface features (i.e., material strength and stiffness properties) as well as the element sizes and shapes at the interfaces. This paper proposes parameter values for zero-thickness elements that will give the same numerical outcomes as those using continuum elements in finite element and finite difference commercial software. The numerical results show good agreement for the computed loads transferred from soil to structure using both methods (i.e., zero-thickness elements and continuum elements at interfaces).